Validitas dan Praktikalitas Media Ruang Baca Interaktif Untuk Pengenalan Huruf Vokal pada Murid dengan Hambatan Intelektual - Ranti, Wahyu Mustika; Taufan, Johandri; Marlina, Marlina; Yuliana, Syari (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The ability to recognize vowels is an important foundation in early reading skills, but students with intellectual disabilities still experience difficulties in understanding letter symbols and connecting them to nouns. This condition indicates the need for interactive, concrete learning media that are appropriate to the characteristics of student learning needs. This study aims to develop and test the validity and practicality of interactive reading room media in recognizing vowels in nouns for students with intellectual disabilities. The study used the Research and Development (R&D) method with the Borg and Gall model which is simplified into five stages, namely initial information collection, planning, initial product development, initial testing, and product revision. The trial subjects consisted of 5 students with intellectual disabilities, 3 teachers as media users, and 3 expert validators including media, material, and language experts. Data were collected through a Likert scale questionnaire and analyzed descriptively quantitatively in the form of percentages. The results showed that the media obtained a very high level of validity with an average score of 91.5% and a practicality level of 95.38%. These findings indicate that interactive reading room media is suitable for use as an alternative for early reading learning which is able to facilitate students in understanding vowels through a more interesting and easy-to-understand learning experience.